Forensic Assessment of Metal Contaminated Rivers in the 21st Century Using Geochemical and Isotopic Tracers - Miller, Jerry (Minerals (Basel), 2013)
Documentation of contaminant source and dispersal pathways in riverine environments is essential to mitigate the potentially harmful effects of contaminants on human and ecosystem health, and is required from a legal perspective (particularly where the polluter pays principle is in effect) in assessing site liability. Where multiple natural and/or anthropogenic sources exist, identification of contaminant provenance has proven problematic, and estimated contributions from a specific source are often the subject of judicial debate. The past, current, and future use of geochemical and isotopic tracers in environmental forensic investigations of contaminant provenance, transport, and fate are analyzed herein for sediment-associated trace metals in riverine environments, particularly trace metals derived from mining and refining operations. The utilized methods have evolved significantly over the past four decades. Of primary significance has been the growing integration of geomorphic and stratigraphic techniques with the use of an increasing number of geochemical tracers including stable isotopes. The isotopes of Pb have been particularly well studied, and have been applied to a wide range of environmental media. Advances in analytical chemistry since the early 1990s have allowed for the precise characterization of other non-traditional stable isotopic systems within geological materials. The potential for using these non-traditional isotopes as tracers in river systems has yet to be adequately explored, but a number of these isotopes (e.g., Cd, Cu, Cr, Hg, Sb, and Zn) show considerable promise. Moreover, some of these isotopes (e.g., those of Cu, Cr, and Hg) may provide important insights into biogeochemical cycling processes within aquatic environments. This review suggests that future environmental forensic investigations will be characterized by an interdisciplinary approach that combines the use of multiple geochemical tracers with detailed stratigraphic, geomorphic, and hydrologic data, thereby yielding results that are likely to withstand the scrutiny of judicial review.